2018
DOI: 10.1109/tpami.2017.2707492
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Optimization for Efficient High-Quality Object Proposal Generation

Abstract: Abstract-We are motivated by the need for a generic object proposal generation algorithm which achieves good balance between object detection recall, proposal localization quality and computational efficiency. We propose a novel object proposal algorithm, BING++, which inherits the virtue of good computational efficiency of BING [1] but significantly improves its proposal localization quality. At high level we formulate the problem of object proposal generation from a novel probabilistic perspective, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…We have demonstrated how to generate a small set (e.g., 1000) of proposals to cover nearly all potential object regions, using very simple BING features and a postprocessing step. It would be interesting to introduce other additional cues to further reduce the number of proposals while maintaining a high detection rate [88,89], and to explore more applications [23-27, 29, 90] using BING and BING-E. To encourage future work, the source code will be kept up-to-date at http://mmcheng. net/bing.…”
Section: Future Workmentioning
confidence: 99%
“…We have demonstrated how to generate a small set (e.g., 1000) of proposals to cover nearly all potential object regions, using very simple BING features and a postprocessing step. It would be interesting to introduce other additional cues to further reduce the number of proposals while maintaining a high detection rate [88,89], and to explore more applications [23-27, 29, 90] using BING and BING-E. To encourage future work, the source code will be kept up-to-date at http://mmcheng. net/bing.…”
Section: Future Workmentioning
confidence: 99%
“…The aim of region proposal is to find the interested regions which potentially contain objects with minimized windows, which is important in multi-object detection tasks. Previous works [6,7] have shown that a simple 8 × 8 feature by computing the normed gradients could be adopted as an efficient region proposal. After binarizing the normed gradients feature, BING could achieve efficient objectness estimation.…”
Section: Region Proposal With Bingmentioning
confidence: 99%
“…And MABO v.s. #WIN means the mean average best overlap for the given #WIN proposals [7]. Hence, a larger DR or MABO value means a better proposal quality.…”
Section: Experiments Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the network topology attributes and social attributes are used to measure the similarity between nodes, and the hierarchical clustering method effectively divides the community [25]. In the process of data transmission, if the mobile device does not have a suitable transmission target, the message will occupy a lot of cache, and the data transmission in the community is likely to wait a long time and cause the delay in transmission [26]. After dividing the community, we need to further establish the weight distribution between nodes and community to reduce the time complexity and overhead cost and construct a set of candidate relay nodes based on the relationship between information forwarders and adjacent nodes.…”
Section: Introductionmentioning
confidence: 99%